Characterization of an Endophytic Strain Talaromyces assiutensis, CPEF04 With Evaluation of Production Medium for Extracellular Red Pigments Having Antimicrobial and Anticancer Properties - Mishra, Rahul Chandra; Kalra, Rishu; Dilawari, Rahul; Deshmukh, Sunil Kumar; Barrow, Colin J.; Goel, Mayurika (Frontiers in Microbiology, 2021)
Considering worldwide demand for colorants of natural origin, utilization of ascomycetes fungi as prolific pigment producer unfolds a novel way to obtain these pigments for various applications including food, cosmetic and medical use. Also, presence of very few natural red pigment alternatives in market attracts the research and industry priorities to unearth novel and sustainable source of red pigment producer. The present work is an attempt to identify novel source of red colour obtained from endophytic fungi isolated from terrestrial and marine habitats. Based upon the fungal capacity for pigment production, seven isolates of endophytic fungi were recognized as prospective pigment producers. Out of all, fungal isolate CPE04 was selected based upon the capacity to produce profuse extracellular red pigment. The isolate was identified as Talaromyces assiutensis employing morphological features and phylogenetic characterization by internal transcribed spacer (ITS) sequences. To understand the chemical behaviour of pigmented molecules, an investigation of chemical profile of fungal culture filtrate dried powder (CFDP) was performed using Ultra high performance liquid chromatography diode array detector mass spectrometry (UHPLC-DAD-MS). In total, eight compounds having pigment and pharmaceutical application were tentatively identified using UHPLC-DAD-MS. Considering the commercial aspect of the stated work, an effort was also made for standardizing the upscaling of pigmented molecule. Investigations were performed for optimum medium and culturing conditions for maximum pigment production. CFDP was found to have significant antibacterial activity against the bacterial pathogensStaphylococcus aureus (MTCC737), Vibrio cholerae (N16961) and methicillin-resistant Staphylococcus aureus (MRSA) (ATCC BAA811). The CFDP showed minimum inhibitory concentration (MIC) at 64 μg /mL, 128 μg /mL and 256 μg /mL against S. aureus, MRSA and V. cholerae. Also, concentrations dependent (50-400μg/mL) anticancer effect on HeLa cancer line was observed having half maximal inhibitory concentration (IC50) at 300μg/mL. The antioxidant potential of CFDP has also been proved with the help of antioxidant assay against 2,2'-azino-bis(3-ethylbenzothiazoline-6-sulfonic acid (ABTS +) radical (IC50 32.01 µg/mL); DNA nicking assay and reactive oxygen species (ROS) generated in HeLa cancer line cells. The CFDP was also found to have no cytotoxicity towards HEK 293 T cell line using Alamar Blue (Resazurin),cell metabolic activity reagent